Harnessing artificial intelligence to improve clinical trial design - Bin Zhang; Lu Zhang; Qiuying Chen; Zhe Jin; Shuyi Liu; Shuixing Zhang (Communications Medicine, 2023)
Artificial intelligence (AI) has unparalleled potential to unlock useful information from real-world data to innovate trial design. Here, we discuss how AI can be used to optimize clinical trial design and potentially boost the success rate of clinical trials.